Nokia network security : solutions handbook - Maxwell, Doug, CCSI (Syngress, 2002)
The book introduces readers to both the basics and the finer points of administering, configuring and securing the Nokia IP-series hardware appliance. It introduces readers to the different hardware models and covers the features associated with each. Installation and setup are covered in detail, as well as installation and configuration of the Check Point firewall on the Nokia system.